Cold-formed steel design - Yu, Wei-wen 1924-; LaBoube, Roger A.; Chen, Helen (Metallurgist) (John Wiley & Sons, Ltd., 2020)
"Since it first published in 1985, Cold-Formed Steel Design has been hailed by professionals around the world as the definitive text for those who design for and work with cold-formed steel. There is no competition when it comes to the extensive coverage of both theory and practice of cold-formed steel construction. This Fifth Edition is updated to reflect the 2016 AISI North American Specification for the Design of Cold-Formed Steel Structural Members. The text has been revised to incorporate the Direct Strength Method (DSM) in the main body of design provisions"